2021
DOI: 10.1007/s10518-021-01169-y
|View full text |Cite
|
Sign up to set email alerts
|

Displacement-based design of precast hinged portal frames with additional dissipating devices at beam-to-column joints

Abstract: The seismic performance of precast portal frames typical of the industrial and commercial sector could be generally improved by providing additional mechanical devices at the beam-to-column joint. Such devices could provide an additional degree of fixity and energy dissipation in a joint generally characterized by a dry hinged connection, adopted to speed-up the construction phase. Another advantage of placing additional devices at the beam-to-column joint is the possibility to act as a fuse, concentrating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…The seismic design and assessment of such buildings may be carried out following both traditional and displacement-based approaches (Biondini and Toniolo, 2009;Biondini et al, 2010;Colombo et al, 2016;Belleri, 2017;Torquati et al, 2018;Belleri and Labò, 2021;Bosio et al, 2020;Sousa et al, 2020). Considering the modelling strategies in the case of new buildings, specific considerations on this structural typology can be found in Magliulo et al (2018Magliulo et al ( , 2021, Gajera et al (2021), Bressanelli et al (2019Bressanelli et al ( , 2021, Rodrigues et al (2021), Zoubek et al 2014, De Stefani andScotta (2022).…”
Section: Introductionmentioning
confidence: 99%
“…The seismic design and assessment of such buildings may be carried out following both traditional and displacement-based approaches (Biondini and Toniolo, 2009;Biondini et al, 2010;Colombo et al, 2016;Belleri, 2017;Torquati et al, 2018;Belleri and Labò, 2021;Bosio et al, 2020;Sousa et al, 2020). Considering the modelling strategies in the case of new buildings, specific considerations on this structural typology can be found in Magliulo et al (2018Magliulo et al ( , 2021, Gajera et al (2021), Bressanelli et al (2019Bressanelli et al ( , 2021, Rodrigues et al (2021), Zoubek et al 2014, De Stefani andScotta (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers to date proposed retrofitting solutions that are applicable to frictional beam-to-column connections (e.g. Martinelli and Mulas, 2010 [3], Santagati et al, 2012 [4], Pollini et al, 2013 [5], Belleri et al, 2017 [6], Magliulo et al, 2017 [7], Hu et al, 2020 [8], Belleri and Labò, 2021 [9], Bai et al, 2022 [10], Quaglini et al, 2022 [11], Sonda and Pollini, 2023 [12]), or that make use of dissipative braces (e.g. Dal Lago et al, 2021 [13]).…”
Section: Introductionmentioning
confidence: 99%
“…Determining the displacement ductility is a challenging task because the structural response often lacks distinct points that clearly define yield and ultimate displacements. Displacement studies have been performed to assess the dissipation capacity of precast structures using different procedures (6,7) . In the present study, the authors have addressed the variation in methods adopted to assess ductility and identified the most appropriate method for their comparison.…”
Section: Introductionmentioning
confidence: 99%